Reconfigurable Materials Based on Photocontrolled Metal–Ligand Coordination. (29th July 2020) - Han, Jianxiong; Huang, Yun-shuai; Yang, Ni; Wu, Si
Abstract : Photoresponsive materials have attracted growing interest because of their potential applications in materials science, such as photoswitches, photopatterning, information storage, and so on. However, there are some challenges for photoresponsive materials for certain applications: 1) Only a few photoresponsive surfaces are transformed into multiple states after photoreactions to adapt to changing environmental conditions; 2) Photoresponsive materials may not function properly in cold environments, especially for gels. To address these problems, we have recently developed photoresponsive materials based on ruthenium (Ru) complexes. Such Ru complexes showed a photoinduced ligand substitution under visible light irradiation. Reconfigurable surfaces that can adapt to environmental changes and photoresponsive organohydrogels that function effectively at sub‐zero temperatures have been fabricated using photoresponsive Ru complexes. Herein, it is demonstrated that based on photocontrolled Ru–ligand coordination, reconfigurable surfaces can be modified for user‐defined functions via visible light irradiation and that photoresponsive gels can function even at –20 °C. As a perspective, Ru‐containing photoresponsive complexes could open up pathways for a variety of applications. Abstract : Herein, two reconfigurable materials based on photocontrolled ruthenium (Ru)–thioether coordination are introduced. The materials show dynamic and reversible properties upon visible light irradiation. The photoresponsive Ru–thioether complexes are used for multifunctional reconfigurable surfaces and antifreeze organohydrogels. Reconfigurable materials based on photocontrolled Ru–thioether complexes could open up pathways for a variety of applications.